CNS Correlates of “Objective” Neuropathy in Alcohol Use Disorder - ZAHR, Natalie M. (Alcohol Clin Exp Res, 2019)
BACKGROUND. Among the neurological consequences of alcoholism is peripheral neuropathy. Relative to HIV or diabetes-related neuropathies, neuropathy associated with Alcohol Use Disorders (AUD) is understudied. In both the diabetes and HIV literature, emerging evidence supports a CNS component to peripheral neuropathy. METHODS. In seeking a central substrate for AUD-related neuropathy, the current study was conducted in 154 individuals with AUD (43 women, ages 21–74) and 99 healthy controls (41 women, ages 21–77) and explored subjective symptoms (self-report) and objective signs (perception of vibration, deep tendon ankle reflex, position sense, 2-point discrimination) of neuropathy separately. In addition to regional brain volumes, risk factors for AUD-related neuropathy, including age, sex, total lifetime ethanol consumed, nutritional indices (i.e., thiamine, folate), and measures of liver integrity (i.e., γ-glutamyl-transferase) were evaluated. RESULTS. The AUD group described more subjective symptoms of neuropathy and were more frequently impaired on bilateral perception of vibration. From 5 correlates, the number of AUD-related seizures was most significantly associated with subjective symptoms of neuropathy. There were 15 correlates of impaired perception of vibration among the AUD participants: of these, age and volume of frontal precentral cortex were the most robust predictors. CONCLUSIONS. This study supports CNS involvement in objective signs of neuropathy in AUD.